SUBSTITUSI TEPUNG TERIGU DENGAN PATI SAGU DALAM PROSES PEMBUATAN CAKE - Rahmayuni '; Usman Pato; Vonny Setiaries Johan; M. Atep Solihin (Universitas Riau, 2012)
The purpose of this study were to determine the effect of substitution of wheat flour with sagostarch on the quality of cake and to obtain the best formulation of making cake. Completelyrandomized design (CRD) was use in this study, which consists of five treatments, each treatmentperformed three replications to obtain 15 units of the experiment. The treatments used were: ST1:wheat flour 80 % and sago starch 20%, ST2: wheat flour 60% and sago starch 40%, ST3: wheat flour40% and sago starch 80%, ST4: wheat flour 20% and sago starch 80%, ST5: wheat flour 0% sagostarch 100%. The results showed that the variation of substitution of wheat flour with sago starchsignificant affected the levels of protein, carbohydrates, aroma, color, flavor, texture, and overallassesment, but did not significant influence the levels of water. The best treatment was ST1 (wheatflour substituted with 20% sago starch) with moisture content of 14.61%, protein 9.01%,carbohydrate 12.76% and evaluating the overall sensory evaluation was liked by panelist.